On the Issue of the Unification of Norms on Jurisdiction in the Field of Civil Proceedings Within the European Union - Elena V. Maystrovich (Èkonomika, Pedagogika i Pravo, 2016)
In this article author examines some issues of norms on jurisdiction unification in the field of civil proceedings within the European Union. Author emphasizes that as a result of the adoption of the new Regulation No. 1215/2012 "Brussels Ibis", which came into force in 2012, rules on jurisdiction in the field of civil proceedings have undergone a number of changes. Article deals with the draft of the proposed amendments and their practical implementation. Amendments, their significance, efficiency and correlation with the projected initially are analyzed.